"تطبيق اسلوب البرمجة الخطية في تعظيم ربحية - دراسة حالة مؤسسة النقل البري بالوادي - " - اسلام, رمضاني; عائشة, كينة; ثلجة, زغومة (جامعة الوادي - University of Eloued, 2023)
"تعتبر المدينة تشكيلة من المراكز والنشاطات المختلفة التي يتفاعل مع العنصر البشري، فهي تحتوي على تجمعات سكنية مستقرة وكبيرة ذات كثافة سكانية مرتفعة وغير متجانسة تنتشر فيها تأثيرات الحياة البرية. إلا أن تميز سكان المدن بالاستقرار والكثافة العالية نج عنه خليط من استعمالات الأراضي المختلفة أدى إلى توطين مراكز النشاط ومختلف الوظائف ،من حيث موقعها ولا يمكن أن تؤدى هذه الوظائف بدون حركة الناس والبضائع ،لذلك نسجت هذه الاستعمالات لنفسها داخل المدينة شبكة من الشوارع والطرق المختلفة لإدامة التفاعل بينها، ولا يتحقق ذلك بدون توفر النقل، فتولدت منه أنواع عديدة منها المجال البري ،ويعتبر النقل البري للمسافرين أحد هذه الأنواع المرتبطة ارتباطا مباشرا بحياة الفرد الذي يسعى دوما لإدراجها في أولويات اهتماماته وذلك بغرض إشباع حاجاته. لقد جاءت هذه الدراسة لتبحث واقع ووضعية شبكة النقل داخل الوسط الحضري لمدينة باتنة وواقع مستوى ونوعية خدمات النقل الجماعي المقدمة من طرف المؤسسة العمومية للنقل البري لسكان الوسط البري لمدينة الوادي ،وتحدد المؤشرات الكمية لشبكة الطرق بتحديد ومعرفة كثافة الشبكة ومدى ترابطها وتغطيتها لمختلف أحياء الوسط البري للمدينة ،والمؤشرات النوعية بمستوى الخدمة لدى المتنقل في النقل البري بمدينة الوادي وهل تحسنت حقا كما هو شائع بعد دخول المؤسسة العمومية للنقل البري قطاع النقل إلى جانب الخواص؟. " "The city is a collection of different centers and activities that interact with the human element, as it contains stable and large residential communities with a high and heterogeneous population density, in which the influences of wildlife are spread. However, the distinction of urban populations with stability and high density resulted in a mixture of different land uses that led to the settlement of activity centers and various functions, in terms of their location, and these functions could not be performed without the movement of people and goods, so these uses woven for themselves within the city a network of streets and different roads to sustain Interaction between them, and this is not achieved without the availability of transport, so many types were generated from it, including the land field, and land transport for travelers is considered one of these types directly related to the life of the individual who always seeks to include it in the priorities of his interests in order to satisfy his needs. This study came to examine the reality and status of the transport network within the urban center of the city of Batna and the reality of the level and quality of mass transport services provided by the public institution for land transport to the residents of the land center of the city of the valley, and determine the quantitative indicators of the road network by identifying and knowing the density of the network and the extent of its interdependence and coverage of the various neighborhoods of the land center of the city And the qualitative indicators of the level of service for the commuter in the land transport in the city of the valley, and did it really improve, as is common after the entry of the public corporation for land transport into the transport sector along with the private ones?"
Keywords: اسلوب البرمجة الخطية، تعظيم ربحية، النقل البري.; Linear programming style, profit maximization, ground transportation.